2005
DOI: 10.1111/j.1365-2184.2005.00339.x
|View full text |Cite
|
Sign up to set email alerts
|

Circadian variation of the cell proliferation in the jejunal epithelium of rats at weaning phase

Abstract: Circadian variation in cell proliferation of the jejunal epithelium of 18-day-old rats was studied using the 2-h arrested metaphase score and crypt isolation method. A continuous decrease in the arrested metaphases occurred from 07.00 h to 13.00 h. From 17.00 h arrested metaphase values increased and were maintained at the higher level during the dark period as showed by Cosinor analyses (P < 0.05). These results indicate that in the young rat there is already a circadian variation in jejunal epithelial cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
7
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
4
7
1
Order By: Relevance
“…This finding could be associated with the introduction of the light/dark cycle during weaning, after the eyes open at around the 14th day after birth. This hypothesis was confirmed in our previous study (Gomes et al,2005), in which it was observed that intestinal epithelial cells show a metaphase index (MI) peak at 15:00 hr during the weaning phase, but the acrophase of MI occurred during the dark period from 21:00 hr to 01:00 hr. This result demonstrated that there is already a circadian variation of the MI at the weaning phase that is influenced by the light/dark cycle.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…This finding could be associated with the introduction of the light/dark cycle during weaning, after the eyes open at around the 14th day after birth. This hypothesis was confirmed in our previous study (Gomes et al,2005), in which it was observed that intestinal epithelial cells show a metaphase index (MI) peak at 15:00 hr during the weaning phase, but the acrophase of MI occurred during the dark period from 21:00 hr to 01:00 hr. This result demonstrated that there is already a circadian variation of the MI at the weaning phase that is influenced by the light/dark cycle.…”
supporting
confidence: 83%
“…Nevertheless, Gomes et al (2005) observed that a circadian variation in the rate of cell proliferation is already present in the jejunal epithelium of rats during the weaning phase. The authors demonstrated that the MI was lower in the morning than in other periods of the day, using the crypt squash method.…”
Section: Discussionmentioning
confidence: 99%
“…This would be possible if the loss of a few cells from the villi is compensated by a concomitant increase in cell proliferation into the crypts. As such, cell migration to the crypt villus junction may have led to the increased villus thickness observed, as the small intestine is an organ that undergoes physiological adaptation according to the diet during its growth, altering cell proliferation, migration and circadian rhythm (Gomes and Alvares, ; Wille et al, ; Gomes et al, ; Soares et al, ). In addition, we suggest that the reduction in goblet cell numbers, caused by physical exercise, may also be related to a change in microbiota in the small intestine that could differ between states of obesity and exercise; however, the hypothesis that physical exercise may change the microbiota of the small intestine needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, the circadian clocks from cyanobacteria to mammals are well-known to gate the different stages of the cell cycle, and thus impose temporal regulation to its progression. In mammals, for instance, S-phase and mitotic index in the oral mucosa, corneal epithelium, digestive tract and even bone marrow exhibit circadian fluctuations [52][53][54][55][56]. In a striking example of cell cycle gating by the clock, the timing of M-phase entry following partial hepatectomy is dictated by the time of day of the procedure [57].…”
Section: The Circadian Clock Cell Cycle Regulation and Dna Damage Rementioning
confidence: 99%